Rhinovirus Detection in Children Hospitalized with Acute Respiratory Illness and Asymptomatic Outpatients. (4th October 2017) - Schuster, Jennifer; Banerjee, Dithi; Hassan, Ferdaus; Boom, Julie; Englund, Janet; Halasa, Natasha; Klein, Eileen J; Mcneal, Monica; Piedra, Pedro; Staat, Mary A; Weinberg, Geoffrey; Williams, John V; et al.
Abstract: Background: Rhinoviruses (HRV) are a leading cause of acute respiratory illness (ARI) in children. Clinical manifestations include asymptomatic, upper, and lower respiratory disease. The objective of this study was to compare symptomatic and asymptomatic HRV detection, as well as symptomatology associated with HRV genotypes (HRV-A, HRV-B, and HRV-C). Methods: Six New Vaccine Surveillance Network sites performed prospective ARI surveillance from 11/1/2015–6/30/2016 and enrolled hospitalized children <5 years (cases) and asymptomatic controls from outpatient clinics. Mid-turbinate and throat swabs were collected and molecular diagnostic testing was performed. Samples positive only for HRV or enterovirus (EV)/HRV were genotyped by amplification and nucleotide sequencing of the VP4/VP2 hypervariable region. Results: HRV or EV/HRV was the sole detected pathogen in 750/4761 (16%) subjects [577/3404 (17%) ARI cases and 173/1357 (13%) controls]. Cases were older than controls (16 vs 11 months, P = 0.003) and more likely to have a history of asthma/reactive airway disease (RAD) (28 vs 1%, P < 0.001), congenital heart defect (5 vs 0%, P = 0.003), or prematurity (25 vs 13%, P = 0.005). Of the 318 HRV genotypes identified thus far, HRV-C was the leading genotype, and children with HRV-C were more likely to be symptomatic cases, P = 0.009 (Table 1). In case patients, symptoms but not underlying medical conditions, differed among the genotypes (Table 2). Conclusion: In hospitalized children with HRV as the only detected pathogen, HRV-C was the most commonly detected type thus far. Admitted children with HRV-C were less likely to be febrile but more likely to wheeze. HRV is an important respiratory pathogen in children <5 years of age, and HRV genotype may play a role in symptomatology and severity, which warrants further investigation. Disclosures: J. Englund, Gilead: Investigator, Research support; CHimerix: Investigator, Research support; Alios: Investigator, Research support; Novavax: Investigator, Research support; MedImmune: Investigator, Research support; GlaxoSmithKline: Investigator, Research support